2017
DOI: 10.1186/s12870-017-1009-3
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid substitutions in the selectivity filter render NbXIP1;1α aquaporin water permeable

Abstract: BackgroundAquaporins (AQPs) are integral membrane proteins that facilitate transport of water and/or other small neutral solutes across membranes in all forms of life. The X Intrinsic Proteins (XIPs) are the most recently recognized and the least characterized aquaporin subfamily in higher plants. XIP1s have been shown to be impermeable to water but permeable to boric acid, glycerol, hydrogen peroxide and urea. However, uncertainty regarding the determinants for selectivity and lack of an activity that is easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The first molecular characterization of plant XIPs demonstrated that NtXIP1;1 from tobacco is localized in the plasma membrane and that its promoter is widely active throughout the plant, both in roots and shoots (Bienert et al., ). In N. tabacum and Nicotiana benthamiana , the transcript of XIP1;1 is spliced in two distinct variants, XIP1;1 α and XIP1;1 β differing in only one amino acid in length (Ampah‐Korsah et al., , ; Bienert et al., ). Toxicity growth assays in the heterologous expression systems Saccharomyces cerevisiae and Pichia pastoris , respectively, suggest that NtXIP1;1α, NtXIP1;1β and NbXIP1;1α function as boric acid channels (Ampah‐Korsah et al., ; Bienert et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The first molecular characterization of plant XIPs demonstrated that NtXIP1;1 from tobacco is localized in the plasma membrane and that its promoter is widely active throughout the plant, both in roots and shoots (Bienert et al., ). In N. tabacum and Nicotiana benthamiana , the transcript of XIP1;1 is spliced in two distinct variants, XIP1;1 α and XIP1;1 β differing in only one amino acid in length (Ampah‐Korsah et al., , ; Bienert et al., ). Toxicity growth assays in the heterologous expression systems Saccharomyces cerevisiae and Pichia pastoris , respectively, suggest that NtXIP1;1α, NtXIP1;1β and NbXIP1;1α function as boric acid channels (Ampah‐Korsah et al., ; Bienert et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of the ar/R region in many plant MIPs subfamilies, like PIPs [ 19 ], TIPs [ 20 ], and XIPs [ 21 ], has been elucidated by the substitution of key amino acids (reviewed by Reference [ 22 ]). However, only a few studies have addressed NIPs, despite being considered as crucial channels for transport of various beneficial (like B and Si), as well as toxic (like As), metalloids in plants [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%